Guidewire and microcatheter utilization patterns during antegrade wire escalation in chronic total occlusion percutaneous coronary intervention: Insights from a contemporary multicenter registry. Issue 4 (17th May 2016) - Karatasakis, Aris; Tarar, Muhammad Nauman J.; Karmpaliotis, Dimitri; Alaswad, Khaldoon; Yeh, Robert W.; Jaffer, Farouc A.; Wyman, R. Michael; Lombardi, William L.; Grantham, J. Aaron; Kandzari, David E.; Lembo, Nicholas J.; Moses, Jeffrey W.; et al.
Abstract : Objectives: We sought to describe contemporary guidewire and microcatheter utilization for antegrade wire escalation (AWE) during chronic total occlusion (CTO) percutaneous coronary intervention (PCI). Background: Equipment utilization for AWE has been variable and evolving over time. Methods: We examined device utilization during 694 AWE attempts in 679 patients performed at 15 experienced US centers between May 2012 and April 2015. Results: Mean age was 65.6 ± 9.7 years, and 85% of the patients were men. Successful wiring occurred in 436 AWE attempts (63%). Final technical and procedural success was 91% and 89%, respectively. The mean number of guidewire types used for AWE was 2.2 ± 1.4. The most frequently used guidewire types were the Pilot 200 (Abbott Vascular, 56% of AWE procedures), Fielder XT (Asahi Intecc, 45%), and the Confianza Pro 12 (Asahi Intecc, 28%). The same guidewires were the ones that most commonly crossed the occlusion: Pilot 200 (36% of successful AWE crossings), Fielder XT (20%), and Confianza Pro 12 (11%). A microcatheter or over‐the‐wire balloon was used for 81% of AWE attempts; the Corsair microcatheter (Asahi Intecc) was the most commonly used (44%). No significant association was found between guidewire type and incidence of major adverse cardiac events (MACE). Conclusions: Our contemporary, multicenter CTO PCI registry demonstrates that the most commonly used wires for AWE are polymer‐jacketed guidewires. "Stiff" and polymer‐jacketed guidewires appear to provide high crossing rates without an increase in MACE or perforation, and may thus be considered for upfront use. © 2016 Wiley Periodicals, Inc.